Multiple cranial nerve schwannomas and meningiomas as a hallmark sign of neurofibromatosis type 2 in a child - Halefoğlu, Ahmet Mesrur (The Turkish Journal of Pediatrics, 2018)
Neurofibromatosis type 2 is a rarely encountered autosomal dominant disorder manifesting with typical radiological findings. These patients have a predilection for development of benign tumors in the central nervous system. Although the presenting symptom is most commonly hearing loss due to acoustic schwannomas, symptoms emanating from other cranial tumors are not uncommon. Herein, we described a 16-year-old male patient presented with multiple meningiomas and cranial nerve schwannomas revealed by magnetic resonance imaging. He fulfilled the diagnostic criteria of neurofibromatosis type 2 and underwent treatment. We emphasized the role of radiology in the early diagnosis of this inherited disorder in order to provide a better prognosis.